Penalaran Forward Chaining dalam Mendiagnosa Penyakit Pada Hewan Pelihara Kucing: - Septilia Arfida; Hariyanto Wibowo; Ketut Artaye; Sri Devi Sopiawati (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The science of information and communication technology, especially the use of mobile devices, is currently growing rapidly every year. Where the growth and level of consumption of information is getting more and more fast. Along with the times, where mobile devices are a necessity that must be owned by everyone to do various things such as communicate, exchange information and do other things. One of the current mobile device operating systems is Android, where the technology is open source so it gets a lot of support. The community's need for technology is very diverse, one of the needs is information media about cat diseases. Cat owners generally do not know the disease that their pet is suffering from, so a system is needed that can imitate the expertise of an expert in solving a problem. The system development model used is the Prototype model. This method starts with gathering user requirements, then makes a quick design which will then be re-evaluated before it is produced properly. The system created uses the Forward Chaining method of reasoning. The Forward Chaining method is a technique for finding conclusions that flows forward, starting with providing some information (facts) which must then be answered according to the facts to be able to determine a final conclusion from the information that has been provided. The results of this study are in the form of an application that can help the community or cat owners in diagnosing diseases in cats and making it easier for users to get information about cat diseases. Keywords : Expert System, Cat, Prototype, Android